Sosialisasi Pengelolaan Lingkungan Yang Bersih di Kota dan Pantai Sabang - Razi, T. Khairol; Maifrizal; Shalahuddin, Muhammad; Wahidanur; Maulida, Dara; Syahputra, Fadli (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
The environment in coastal communities in Sabang City Beach is often contaminated by scattered waste. Potential causes include the habit of people throwing household waste on the beach or waste from other areas carried by sea currents. However, maintaining environmental cleanliness and health must be a top priority for coastal communities. This is not only important for their survival, but also for all marine life around the beach. The purpose of this article is to illustrate that community service activities can change people's views on the cleanliness of the coastal environment and household waste management. The activity method includes systematic planning, implementation, and follow-up reporting. In an effort to change people's views, community service activities produce educational media in the form of leaflets, aimed at providing a deep understanding of environmental cleanliness and waste management. Direct socialization is carried out to the community around the beach, providing broad knowledge about beach cleanliness and household waste management. The results of this activity include changes in people's views on the cleanliness of the coastal environment, as seen from increased understanding and awareness. Educational media in the form of leaflets is an effective tool for conveying information about the cleanliness of the coastal environment that is easily understood by the community. Socialization to the community around the Sabang City beach makes a positive contribution to the cleanliness of the coastal environment and effective household waste management.